Analisis Business Model Canvas (BMC) Mie Tjap Tiga Anak Desa Wlahar Kulon Kecamatan Patikraja Kabupaten Banyumas - Rina Dwi Lestari; Yusuf Enril Fathurrohman (UM Purwokerto Press, 2021)
This study aimed to analyze the design of the canvas business model of the Tjap Tiga Anak Noodle Factory. The method used was the descriptive-analytical method because, in this study, a qualitative research type was chosen to analyze the Business Model Canvas to map the business state at the Mie Tjap Tiga Anak Factory. The results of research, at the Mie Tjap Tiga Anak Factory using a business model canvas, showed business activities in 9 elements, namely customer segments with B2C and B2B, value propositions that were certified halal (LPPOM MUI), channels used were direct and indirect, customer relationships with apply personal assistance, revenue streams were product sales, key resources were human resources, key activities were production activities, key partnerships were carried out with the government, distributors, and the community or customers, and the cost structure includes fixed and variable costs.